Cascade-Gain-Switching for Generating 3.5- $μ$ m Nanosecond Pulses From Monolithic Fiber Lasers - Jianlong Yang; Haizhe Zhong; Shuaiyi Zhang; Yulong Tang; Dianyuan Fan (IEEE Photonics Journal, 2018)
We propose a novel laser configuration that can output 3.5- $μ$ m nanosecond laser pulses based on a simple and monolithic fiber structure. Cascade-gain-switching (CGS) converts the wavelength of nanosecond pulses from 1.55 to 3.5 $μ$ m by two successive gain-switching processes. CGS eliminates the requirement of using bulky free-space modulators for Q-switching. With a well-established theoretical model, we investigated the feasibility of this novel configuration and thoroughly explored its characteristics. In single-shot regime, the pulse width of the 1.55- $μ$ m pump has major impact on the temporal shape of the intermediate 1.97- $μ$ m pulse while has neglected influence on the generated 3.5- $μ$ m pulse. On the other hand, increasing the continuous-wave (CW) pump power can significantly improve the output peak power and shorten the pulse when the pump power is less than $\sim 4$ W. In the repetitive-pulse regime, we found the maximum repetition rate is positively correlated the CW pump power. With a typical CW pump power of 5 W, the 3.5- $μ$ m pulse train can be stably outputted when the repetition rate is $<=100$ kHz.